Shear effects on hollow section piers under seismic actions: experimental and numerical analysis - Raimundo Delgado (2009)
Shear effects are often a very important issue on the seismic behaviour of piers, particularly for hollow section bridge piers. In fact, for this type of piers the cyclic response is similar to that of a structural wall in which both the transverse reinforcement ratio and the detailing can play an important role on its performance, even likely to be determinant in terms of the failure mechanism. On the other hand, codes and design guidelines are usually very conservative concerning shear capacity in order to avoid any shear failure mechanism likely to trigger well known catastrophic consequences. Therefore, research studies on this topic are still needed for a better understanding of pier cyclic shear response and also for improvement of the performance under seismic actions. Pursuing this general objective, this paper partially reports on an experimental/numerical campaign carried out on 1:4 reduced scale bridge piers in order to highlight and investigate shear-type problems. Within the scope of this paper, two specimens types were selected having equal rectangular hollow section (900 x 450 mm(2), 75 mm thick) but different transverse reinforcement detailing, namely one with a single stirrup per wall (representative of typical bridge construction without seismic design requirements) and another with multiple stirrups, according to Eurocode 8 provisions. Numerical simulations of the experimental results were also conducted aiming at contributing for complete and consistent interpretations of experimental results. Detailed modelling was performed allowing for realistic simulations of the non linear behaviour, particularly suitable when a significant shear component is involved. Therefore, the numerical strategy was based on a detailed 3D FEM discretization using a two-scalar variable damage model for the concrete constitutive law and a suitable cyclic behaviour law for steel bars represented by truss elements. Results have shown that shear deformation and failure modes are well simulated, while providing detailed insight concerning concrete damage pattern and distribution of yielding on the transverse and longitudinal reinforcement.